THE EFFECT OF ENERGY DRINKS ON THE MORPHOLOGY OF OVARIES AND TESTES: MODERN DATA AND MECHANISMS OF INFLUENCE - Ismatova , M.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
This article analyzes the effect of energy drinks on the morphology of the ovaries and testes. Based on the results of experimental and clinical studies, it has been established that the components of these drinks—caffeine, taurine, and other biologically active substances—induce changes in reproductive tissues. In women, ovarian stromal and follicular apparatus degeneration, folliculogenesis disorders, and endocrine dysfunction have been observed. In men, a decrease in the spermatogenesis process, atrophy of the testicular tubules, and a reduction in Sertoli and Leydig cell proliferation indices have been recorded. Experiments on animals have shown that long-term consumption of energy drinks leads to impaired blood supply to the ovaries and testes, microvascular changes, and increased apoptotic processes. Morphological, histological, and biochemical studies have enabled the identification of biological markers of these processes. The results obtained allow for the assessment of the impact of energy drinks on reproductive health and the prediction of pathological processes in advance.